Facilities Management Service Providers Competencies Reviews for Managing Green Buildings in Malaysia - Ismail, Siti Nur Ayunie; Ishak, Mohd Hafizal (Journal of Technology Management and Business, 2021)
Competence can be described as an individual's aptitude or capability to perform a task effectively. Competencies utilise job-related behaviour, motivation, and technical knowledge to ensure that all employment needs are met. Therefore, there is a list of competencies reserved for managing green buildings. However, there are still green buildings that are not well managed, and this is closely related to the level of competencies of a facility manager who manages the green building. This paper aims to determine the competency elements of facilities management service providers in managing green buildings. The qualitative method through document review with content analysis was used on selected previous research related to the topic. The five main facilities management service provider competencies in managing green buildings were defined as sustainable procurement, sustainable operations, resource management, repair and maintenance, and environmental health. The results are expected to reveal evidence that a framework, guideline, or specific training is needed to improve facilities management skills in future research.